Peningkatan Hasil Belajar Siswa Dalam Materi Transformasi Geometri Melalui Model Problem Based Learning (PBL)(PTK Kelas XI Multimedia SMKNegeri 9 Surakarta Tahun 2014/2015 ) - Siregar, Indra Ivanti, Idris Harta, M.A., Ph.D (2015)
This research aims to improve the results of students' mathematics learning through Problem Based Learning model.This type of research is a classroom action research conducted at SMK Negeri 9 Surakarta. Subject recipient of the action were students of class XI Multimedia C totaling 29 students, and the subject of implementing measures is a researcher and teacher math class XI C. Multimedia Techniques of data collection is done by observation, documentation, test methods, and field notes. To ensure the validity of data used triangulation techniques. The technique of data validity checks done by increasing students' mathematics learning outcomes seen from indicators: (1) Value of students in independent practice given above KKM is 67, prior to the act of 46.67% increased to 83.33% at the end of the action. (2) The ability of student skills by applying concepts / principles and problem solving strategies prior to the act of 31.03% increased to 82.75% at the end of the action. From this study it can be concluded that the application of problem based learning model can improve mathematics learning outcomes. Keyword: Learning OutcomesMathematics, Problem Based Learning.